Twenty-four-hour low energy availability induced by diet or exercise exhibits divergent influences on sleep and recovery indices among female and male cyclists - Smith, E. S.; Kuikman, M.; Rusell, S.; Gardiner, C. L.; Halson, S. L.; Stellingwerff, T.; Harris, R.; McKay, A. K. A.; Burke, L. M. (Medicine & Science in Sports & Exercise, 2025)
Purpose To examine the effects of 24-h manipulations in energy availability (EA), through altering energy intake (EI) or exercise energy expenditure (EEE), on sleep characteristics and nocturnal heart rate variability (HRV).